Digital Administration and Religious Diversity Management: Digital Records Processing and Electronic File - Pelayo Olmedo, José Daniel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
On march 30th, 2021, Royal Decree 203/2021, approving the regulation of action and operation of the public sector by electronic means (hereinafter RD 203/2021) was enacted. It was the last step of the Spanish administration transition to the implementation of e-resources and tools on its daily activity. This transition begun with the earlier article 45 of the Law 30/1992, but was definitively settled by Law 39/2015, of October 1st, on the Common Administrative Procedure of Civil Services (hereinafter Law 39/2015) and Law 40/2015, of October 1, of the Legal Regime of the Public Sector (hereinafter Law 40/2015). Both transformed what was initially conceived as the civil service’s commitment to incorporate «technical means» into a guarantee of the citizen’s right to relate electronically with the administration, simplifying its access, reinforcing its use and trying to improve the efficiency of administrative management. At the same time, religious diversity management units consolidated its adaptation and update their regulations and procedures, after 34 years in force, to the new reality. Undoubtedly, a step forward was taken, but one part still remains: to consolidate the digitalization process of the administration and its consequences in their regulation. This paper will be focused on the analysis, explanation and application of the e- government structural principles, resources and fundamental tools to the religious diversity management bodies. To do so we will take, as a reference, the constitutional perspective where elements such as the rights to hearing and participation of the citizen in the administrative procedure are guaranteed (art. 105 CE) and the commitment of the State regarding the exercise of the right to ideological and religious freedom leads the way to understand the Spanish model and its regulatory and civil services framework (art. 9.2 and 16 CE). But, mainly, we will focus on the e-procedure regulation, the use of common resources such as the General Access Point, the Personal authorized electronic address, the identification, authentication and registration systems, the e-communication and notification systems, as well as the creation, transmission and conservation of e-documents. Consequently, this will allow us to identify strengths and necessary improvements.
Keywords: religious diversity management; digital administration; e-government; electronic registration systems; e-documents; electronic records; electronic file